Association between cardiometabolic index and infertility among American women aged 20–45 years: a cross-sectional analysis from 2013–2020 NHANES data - Liu, Yanyun; Ying, Gefei; Chen, Zhen; Liang, Hongping; Yu, Junhui (BMC women's health, 2025)
Background While metabolic syndrome and obesity are established risk factors for infertility, previous studies have neglected age-specific analyses and nonlinear associations, particularly in women aged 20–45 years, a critical demographic for fertility and metabolic health. Therefore, this study aimed to examine the nonlinear relationship between Cardiometabolic Index(CMI) and infertility risk in US women of reproductive age (20–45 years) using nationally representative the National Health and Nutrition Examination Survey(NHANES) data (2013–2020). Methods Cross-sectional data from the 2013–2020 NHANES were used to analyse 3,613 women aged 20–45 years with complete CMI and infertility data. Infertility is defined as the inability to conceive after at least 12 months of regular unprotected intercourse.The CMI was calculated using waist circumference(WC), height, triglyceride(TG), and high-density lipoprotein cholesterol (HDL-C). Multivariate logistic regression analysis, supplemented by smooth curve fitting and threshold effect analysis, was used to assess the association between CMI and infertility. Results The mean age of the subjects was (32.8 ± 7.5) years and 488 (13.51%) of them reported infertility. CMI < 0.59 were highly correlated with risk of infertility(OR = 4.47, 95%CI: 2.19–9.15, P < 0.0001), whereas CMI ≥ 0.59 was not significantly associated with the risk of infertility (OR = 1.01, 95%CI: 0.81–1.24, P = 0.9621). Conclusion Our results show a significant positive non-linear relationship between CMI and infertility risk in US women aged 20–45, with a threshold effect.